Landscapes and landforms of Western Canada - Slaymaker, Olav (Springer, 2017)
This is the only book to focus on the geomorphological landscapes of Canada West. It outlines the little-appreciated diversity of Canada's landscapes, and the nature of the geomorphological landscape, which deserves wider publicity. Three of the most important geomorphological facts related to Canada are that 90% of its total area emerged from ice-sheet cover relatively recently, from a geological perspective; permafrost underlies 50% of its landmass and the country enjoys the benefits of having three oceans as its borders: the Arctic, Pacific and Atlantic oceans. Canada West is a land of extreme contrasts -- from the rugged Cordillera to the wide open spaces of the Prairies; from the humid west-coast forests to the semi-desert in the interior of British Columbia and from the vast Mackenzie river system of the to small, steep, cascading streams on Vancouver Island. The thickest Canadian permafrost is found in the Yukon and extensive areas of the Cordillera are underlain by sporadic permafrost side-by-side with the never-glaciated plateaus of the Yukon. One of the curiosities of Canada West is the presence of volcanic landforms, extruded through the ice cover of the late Pleistocene and Holocene epochs, which have also left a strong imprint on the landscape. The Mackenzie and Fraser deltas provide the contrast of large river deltas, debouching respectively into the Arctic and Pacific oceans.
Keywords: Landforms -- Canada.; Geomorphology -- Canada.; Canada.; elektronické knihy; electronic books